Defining the needs of patients with recurrent and/or metastatic head and neck cancer: An expert opinion. (January 2021) - Oliveira, Thiago Bueno; Mesía, Ricard; Falco, Agustin; Hsieh, Jason Chia-Hsun; Yokota, Tomoya; Saada-Bouzid, Esma; Schmitz, Sandra; Elicin, Olgun; Giacomelli, Luca; Bossi, Paolo
Graphical abstract: Highlights: Patients with RM HNC show different symptoms and needs. Addressing the above needs is crucial in all patients with HNC. However, research on how to address patients' needs in RM-HNC is scarce. This paper discusses patients' needs for RM HNC. Prospective evaluations embracing all those needs could be implemented. Abstract: The clinical and biological heterogeneity of head and neck cancer (HNC) is paralleled by a plethora of different symptoms that affect the patient's quality of life. These symptoms include, for instance, pain, fatigue, nutritional issues, airways obstruction, voice alterations and psychological distress. In addition, patients with HNC are prone to a high risk of infection, and may also suffer from acute complications, such as hypercalcemia, spine compression by bone metastasis or bleeding. Prolonging survival is also an inherent expectation for all patients. Addressing the above needs is crucial in all patients with HNC, and especially in those with recurrent and/or metastatic (RM) disease. However, research on how to address patients' needs in RM-HNC remains scarce. This paper defines patients' needs for RM HNC and presents an Expert Opinion on how to address them, proposing also some lines of research.